Cardiovascular event rate and death in high‐risk secondary prevention patient cohort in Finland: A registry study. Issue 4 (15th March 2022) - Toppila, Iiro; Ukkola‐Vuoti, Liisa; Perttilä, Julia; Törnwall, Outi; Sinisalo, Juha; Hartikainen, Juha; Lehto, Seppo
Abstract: Background: A large number of patients are living with atherosclerotic cardiovascular (CV) disease and thus are at risk of life‐threatening CV events. Hypothesis: This study evaluated the risk for a recurrent CV event or death in Finnish real‐world data. Methods: Patients with an incident atherosclerotic CV event between 2012 and 2016 were included in this retrospective registry study and followed for recurrent CV events or death. The risk and risk factors of recurrent CV events or death and time from the first CV event to recurrence were assessed. Results: A total of 48, 405 patients were followed from their first CV event. The event rate was 14.34 events per 100 patient‐years. Multistate models suggested that at 5 years post index CV event, 41.5% of the patients had died or suffered a recurrent CV event. Death was the most common type of subsequent event (61.5%). After the first CV event, there were rapid increases both in recurrent CV events and deaths during the next 6 months. The subsequent CV event was usually of the same type as the first, which was of the cardiac or cerebrovascular cluster. Conclusions: The incidence of recurrent CV events and all‐cause mortality was high in patients suffering from their first CV event, particularly during the first 6 months after the index event. Death was the most common subsequent event. The event rate accelerated after each additional CV event. This suggests that the acute treatment of the index event should be followed by prompt secondary prevention measures to achieve guideline‐recommended goals as soon as possible. Abstract : Risk for a recurrent cardiovascular event or death in Finnish real‐world Data.